An ingenious MMC topology appropriate for motor drives across their entire frequency spectrum - Manoj Dhondiram Patil; Mohan P. Thakre; Haridarshan S. Sonawane; Pawan C. Tapre; Sunil Somnath Kadlag; Deepak P. Kadam (Institute of Advanced Engineering and Science, 2023)
Modular multilevel converter (MMC) modules have popped up as among the best choices for medium and high-powered uses. This paper proposes a control scheme for the entire frequency range of operation for the MMC, focusing on supplying a three-phase machine. The machine is required to be controlled in the outer as well as the inner loop. Standard field oriented control (FOC) manages the three-phase machine in the outer closed loop while the inner control has to come up against the problem of energy balancing. That is unevenly distributed and stored in the capacitance of the upper and lower arms of the converter. There are two operating methods used in the inner control loop: a low-frequency method is used for start-up and low-speed operation, and a high-frequency method is for higher speed. In low-frequency mode (LF-mode), a special control strategy has to be implemented to minimize the energy oscillation in the capacitances of the converter arms. It makes utilization of the 3-phase machine's common mode voltage (Vc) as well as internal circulatory currents to verify a symmetrical energy distribution inside this MMC arms and also to avert whatever AC currents inside the DC source.